Obesity and acylcarnitine derivates interplay with coronary artery disease - Tomasz Urbanowicz; Paweł Gutaj; Szymon Plewa; Ievgen Spasenenko; Anna Olasińska-Wiśniewska; Beata Krasińska; Andrzej Tykarski; Aleksandra Krasińska-Plachta; Łucja Pilaczyńska-Szcześniak; Zbigniew Krasiński; Ewelina Grywalska; Mansur Rahnama; et al. (Scientific Reports)
Abstract Coronary artery disease (CAD) is common in patients burdened with metabolic syndrome. Increased risk of cardiovascular disease is associated with abnormal levels of acylated derivates of carnitine. The present study aimed to evaluate the possible association between carnitine derivatives and coronary artery disease, including obese individuals. Twenty consecutive patients presenting with dyspnea on exertion were enrolled in the prospective analysis for metabolomic profiling. They were divided into two groups regarding CAD presence. Six (60%) men and four (40%) women comprised the CAD group assigned as Group 1, while 6 (60%) men and 4 (40%) women with normal coronary arteries on angiograms as Group 2. Compared to the non-CAD group, the CAD group was characterized by lower levels of the sum of long-chain ACs (p = 0.024), the sum of short-chain ACs (p = 0.022), saturated fatty acids (SFA) (p = 0.030) and monounsaturated fatty acids (MUFA) (p = 0.022). Further subanalysis concerning patients’ body mass index and CAD showed significant differences in plasma sum of ACs between the groups (p = 0.050) and SFA (p = 0.050) but not regarding the short-chain ACs (p = 0.060), medium-ACs (p = 0.758), long-chain-ACs (p = 0.141), or MUFA (p = 0.151). Our analysis revealed lower plasma levels of short-chain and saturated fatty acids acylcarnitine derivates in obese patients presenting with CAD.